Law Enforcement of Middlemen in the Crime of Narcotics Group I Not Plants - Katryn NN Pakpahan; Janpatar Simamora; Jinner Sidauruk (Greenation International Journal of Law and Social Sciences, 2024)
The use of narcotics, psychotropic substances and other addictive substances has a huge impact if misused. However, on the other hand, these substances can provide benefits for the development of science and the treatment of disease if used according to the instructions of the authorities. Therefore, this scientific legal work discusses two main things: first, how the legal regulations relate to intermediaries in the sale and purchase of class I non-plant narcotics according to positive law, and second, how to apply criminal law to these perpetrators. This research uses a normative method with a statutory approach. Eradicating narcotics faces very complex obstacles, ranging from internal and external factors of perpetrators to the involvement of law enforcement officers in abuse. As a solution, the government needs to optimize the role of society to increase supervision and legal awareness, revise narcotics laws, and tighten supervision of the morality of law enforcement officers.